Hypervalent-iodine-mediated base-free oxidative olefination of benzylic amines to access α,β-unsaturated ketones - Rupanawar, Bapurao D.; Bansode, Ajay H.; Suryavanshi, Gurunath (Synlett, 2025)
We report a one-pot base-free protocol for the oxidative olefination of benzylic amines promoted by a hypervalent iodine reagent for the synthesis of alpha,beta-unsaturated ketones. Mechanistically, (diacetoxyiodo)benzene oxidizes the benzylic amine to the corresponding imine, which, on reaction with a phenacyl(triphenyl)phosphonium bromide salt and an in situ generated acetoxy anion leads to an alpha,beta-unsaturated ketone. A wide range of alpha,beta-unsaturated ketones were easily accessed through direct oxidative olefination of substituted benzylic amines in good to excellent yields and with high E -selectivity.
Keywords: benzylic amines; enones; hypervalent iodine; olefination; Oxidation